A Resistance-Nodulation-Cell Division Family Xenobiotic Efflux Pump in an Obligate Anaerobe, Porphyromonas gingivalis - Ikeda, Takeshi (American Society for Microbiology, 2002)
Porphyromonas gingivalis, a gram-negative obligate anaerobe, contains two homologs of an Escherichia coli resistance-nodulation-cell division-type multidrug exporter gene, acrB, in putative operons, together with homologs of membrane fusion protein gene acrA and outer membrane channel gene tolC. MIC determination and accumulation assays with mutants with disruptions of one or more genes showed that one cluster, named xepCAB, pumped out multiple agents including rifampin, puromycin, and ethidium bromide.